Implementasi Kebijakan Pendidikan Di Kabupaten Merauke (Analisis Undang-Undang Nomor 20 Tahun 2003 Tentang Sistem Pendidikan Nasional) - Thalib, Najda; Haris, Umiyati (Jurnal Administrasi Karya Dharma, 2023)
Education is one of the rights guaranteed by the law and is a goal of the state, which is to educate the nation's life. This makes education one of the main pillars for the strength of the nation and the state. The government issues policies through Law Number 20 of 2003 concerning the National Education System. This aims to address the challenges and issues of basic and secondary education, which is the obligation of every child in Indonesia to participate in. This research discusses the implementation of Law Number 20 of 2003 concerning the National Education System. The purpose of this research is to describe and analyze the implementation of Law 20/2003, which is examined through the Grindle policy implementation model. This research is qualitative research with a descriptive-analytical data analysis method. Data is presented descriptively and then analyzed using policy analysis to obtain valid data regarding the implementation of education policies in addressing the access gap to education in Merauke Regency. Data is obtained through literature review by reviewing official documents such as policy texts, official websites, and scholarly articles. Data analysis techniques use the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results of the research show that the implementation of education policies in Merauke Regency is less effective. This is due to the lack of deployed resources, insufficient actor strategies, and the lack of compliance and responsiveness from implementers.